PENGARUH INFLASI DAN NILAI TUKAR TERHADAP PROFITABILITAS BANK UMUM SYARIAH YANG LISTING DI OJK TAHUN 2016-2020 - Asniza Afhami; Maslichah Maslichah; Harun Alrasyid (Universitas Islam Malang, 2021)
This study aims to determine the effect of inflation and exchange rates on theprofitability of Islamic Commercial Banks listed at OJK in 2016-2020. The analyticalmethod used in this research is multiple linear regression analysis. for hypothesis testingusing SPSS. The results of this study indicate that 1) the inflation variable has asignificant negative effect on profitability (Y). 2) the exchange rate variable has no effecton profitability (Y). while the inflation and exchange rate variables affect profitability.